Hubungan Ketuban Pecah Dini dengan Kejadian Kala II Lama pada Ibu Bersalin di RSUD Abdul Moeloek Provinsi Lampung - Tri Lamtiur Pakpahan; Ratna Dewi Puspita Sari; Sutyarso; Rodiani (Majority, 2021)
Prolonged second-stage labor is one causes of the maternal mortality rate (MMR) in the world. The average lenght of labor in the world causes maternal mortality by 8% and in Indonesia by 9%. Maternal mortality is most often occurs during childbirth, one of the causes is the long second stage (37%) and perinatal death itself is one of the causes is asphyxia in infants (28%). The purpose of this study was to determine the relationship of Premature Ruptur of Membrane with the events of the old stage II of maternity mothers. The method used in this study uses observational analytic methods with cross sectional design. A total of 69 patients were selected by consecutive sampling technique. The date was collected from medical records of patients in the midwifery room Dr. H. Abdul Moeloek Lampung Province. The inclusion criteria of this study were mothers aged 18-40 years with term gestational age and having KPD. Patients who were accompanied by birth defects, fetal abnormalities and parturition with conditions of sectiocesarea were excluded from the study sample. The results showed that as many as 37 patients (72.6%) who experienced premature rupture of membrane at the time of the inpartu showed an old stage II event and as many as 8 patients (44.4%) patients who experienced premature rupture of membrane when not before the party showed the event of the old stage II. Based on the Chi-square test, the value of p = 0.031 (p